THE METHODOLOGICAL ASPECT OF USING ASSOCIATED EXERCISES FOR WORKING WITH WIMMELBUCH AT ENGLISH LESSONS IN PRIMARY SCHOOL - Лобачова, Ірина (Професіоналізм педагога: теоретичні й методичні аспекти, 2018)
The article describes the methodological aspect of using associative exercises for working with illustrative material of Wimmelbuch at English lessons in primary school. It is found out that much attention is given to teaching a foreign language to schoolchildren at the age between six and seven whose age characteristics determine moving and motor activity and a significant role of the nonverbal component in self-expression. It is determined that non-verbal actions play an important part in communication and have a significant influence on the partner, so this fact should be taken into account while teaching foreign language communication. The purpose of the study is to find out the didactic conditions for using associative exercises to work with the Wimmelbuch at English lessons in primary school. The relevance of the outlined problem is determined by the lack of development of the intercultural and activity approaches to the issue of using associative exercises to work with the Wimmelbuch for conducting intercultural communication. The article proves that the illustrative materials of the Wimmelbuch helps to realize the principles of the concept of personality’s development in cross-cultural activity, that meets the requirements of modern society to the level and quality of foreign language education. By using associative exercises while working with the Wimmelbuch at English lessons, the conditions are created for developing primary schoolchildren’s language abilities and for training them for real communication within intercultural contacts, in which it is necessary to understand and use not only verbal but also non-verbal means of communication. The associative exercise is specially organized training which is performed by using a large number of different analyzers (visual, auditory, speech-motor and moving). Such exercises give an opportunity to solve the main problems of teaching a foreign language to primary schoolchildren, because it is based on the actual theory of language learning through the personal activity of a child. The use of non-verbal associative symbols at foreign language lessons allows a student to perceive language material through all analyzers, and the student’s need for moving activity is fully ensured. Methodical tasks of the associative exercises are defined as to extend language abilities of students within the communicative minimum; to make studying a foreign language interesting, that will develop a student’s positive attitude to learning; to bring studying a foreign language closer to free communication; to involve the language experience of students’ communication in their native language to transfer it to communication in a foreign language and vice versa; to train moral qualities and culture of communication; to acquaint students with the peculiarities of socioculture of a foreign country, etc.